Testing ideation performance on a large set of designers: effects of analogical distance. Issue 1 (2nd January 2020) - Jia, L.; Becattini, N.; Cascini, G.; Tan, R.
ABSTRACT: This paper reports an experiment that aims at providing new evidence to reinforce contradictory conclusions, as available in engineering design literature, on the effect of analogical distance on ideation performance of designers. The experiment involved 84 graduate students in Mechanical Engineering, with typical competencies on engineering design, but without any specific skill on analogy-based idea generation. The subjects were exposed to three different treatments (near-, medium-, far-field analogies) whose design performance has been compared to a control group. The observation confirms that designers not specifically trained in designing-by-analogy get benefit from sources of inspiration that share the same (sub-)functions and context of the target system, as their idea generation process lead to ideas having higher novelty and quality compared to the outcomes of subjects exposed to more distant analogies. The observed results also show that the exploration of the design space gets positively affected.